Dietary acid load and lung cancer risk: A case-control study in men. (2021) - Ronco, Alvaro L.; Martínez-López, Wilner; Calderón, Juan M.; Golomar, Wilson
Highlights: Dysregulation of acid-base balance can contribute to inflammation and cancer development. There is scarce epidemiologic evidence linking diet-dependent acid load and cancer risk. The study reports direct associations between dietary acid load and lung cancer risk. To our knowledge, this is the first report on the quoted epidemiologic relationship. ABSTRACT: Background: Dysregulation of the endogenous acid-base balance can contribute to inflammation and cancer development if metabolic acidosis is sustained. The epidemiologic evidence on the association between diet-dependent acid load and cancer risk is scarce and inconsistent. We aim to explore the possible role of dietary acid load in lung cancer (LC) risk. Methods: A case-control study was performed on 843 LC cases and 1466 controls by using a multi-topic questionnaire, including a food frequency questionnaire. Controls were matched to cases by age-frequency, urban/rural residence, and region. Food-derived nutrients were calculated from available databases. The dietary acid load was calculated using validated measures as potential renal acid load (PRAL) score and net endogenous acid production (NEAP) score. Odds ratios (ORs) were estimated by logistic regression. Results: We found direct associations between dietary acid load and LC risk. The highest quartile of the NEAP score was significantly associated (OR=2.22, ptrend <0.001). The PRAL score displayed similar associations in simpler regression models, but there was no association when a more complex one was used (OR=0.99, ptrend =0.94). The NEAP score was associated with a significant risk increase in all cell types, except for small cell cancers, but the PRAL score did not show any association. Conclusions: The NEAP scores, directly associated with meat intake and inversely associated with plant-based foods intake, suggest that a high acid load dietary style may increase LC risk. Studies focused on food groups, and nutritional patterns are in line with our findings. Although the data shown here represent the first one to be published on this issue, further studies are needed to confirm these findings.